ETIKA DAN PRIVASI LAYANAN JASA TEKNOLOGI FINANSIAL: Studi Fenomenologi Pada Korban Pelanggaran Privasi - Sanjaya, Rati; Irwansyah, Irwansyah (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
Digitalization not only help people to make life easier, but also brought data risk. Data became a commodity in industry 4.0 that made ethic and privacy issue for financial technology (fintech). Rapid technology development unequal with regulation development, Indonesia still use stock exchange’s law which not covered all financial technology aspect like cyber security. This research was made to discover privacy violation that happened to two key informants and three informants who support this research to figure the case through phenomenology. The result is fintech user was lack of knowledge about privacy and threat that might be happened about data they give to fintech organization. To cite this article (7th APA style): Sanjaya, R. & Irwansyah (2019). Etika dan Privasi Layanan Jasa Teknologi Finansial: Studi Fenomenologi pada Korban Pelanggaran Privasi [Ethics and Privacy regarding the Financial Technology Services]. Journal Communication Spectrum, 9(1), 14-29. http://dx.doi.org/10.36782/jcs.v9i1.1873